Effect of Rare Earth Y on Properties of Nanosized 90W-7Ni-3Fe Composite Powder Fabricated by Spray Drying-Hydrogen Reduction. (12th February 2008) - Ma, Y.-Z.; Wensheng, Liu; Baiyun, Huang; Jinglian, Fan
Abstract : (W, Ni, Fe) composite oxide powder synthesized by spray drying was reduced at 700 ∘ C for 90 minutes inH 2 atmosphere. The effect of rare earth Y onH 2 reduction of (W, Ni, Fe) composite oxide powder was studied. Phase composition, crystalline size, and particle morphology of the reduced powder have been measured by X-ray diffraction and scanning electron microscope (SEM). Fsss particle size and special surface area of the reduced powder were also measured and analyzed. The result showed that new phaseY(N i 0.75 W 0.25 ) O 3 appeared in the reduced powder and particle morphology was nearly spherical or polyhedron by Y additions. The higher the rare earth element content was, the bigger the influencing on particle morphology was. When the rare earth Y content was under 0.8%, with the increase of the rare earth element content, d BET, Fsss, and crystal sizes of the reduced powder decreased greatly.